2023
DOI: 10.17219/dmp/151577
|View full text |Cite
|
Sign up to set email alerts
|

Orthodontic treatment need, the types of brackets and the oral health-related quality of life

Judith Patricia Barrera-Chaparro,
Sonia Patricia Plaza-Ruíz,
Karen Lorena Parra
et al.

Abstract: Background. Malocclusion can affect the oral health-related quality of life (OHRQoL). The influence of the orthodontic treatment need (OTN) and the type of brackets on OHRQOL is not clear. Objectives.The aim of the present study was to determine the relationships between OTN and the bracket type and OHRQoL during the first 6 months of orthodontic treatment (OT) in adult patients.Material and methods. This cohort study was conducted at the Department of Orthodontics of a private university. A total of 216 patie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 35 publications
0
3
0
Order By: Relevance
“…Orthodontic treatment can significantly improve patients’ OHRQoL [ 19 , 23 , 24 , 29 ]. In this study, in the total sample, it was observed that at one month after starting treatment, the patients’ OHRQoL was worse than at the beginning.…”
Section: Discussionmentioning
confidence: 99%
“…Orthodontic treatment can significantly improve patients’ OHRQoL [ 19 , 23 , 24 , 29 ]. In this study, in the total sample, it was observed that at one month after starting treatment, the patients’ OHRQoL was worse than at the beginning.…”
Section: Discussionmentioning
confidence: 99%
“…Another crucial area affected by HRT is bone health ( Vermesan et al, 2015 , Henes and Hübner, 2020 ). Estrogen has been found to have a protective effect on blood vessels and can help maintain cardiovascular health in premenopausal women ( “The 2022 Hormone Therapy Position Statement of The North American Menopause Society”, 2022; Barrera-Chaparro et al, 2023 ). However, the impact of HRT on cardiovascular health is complex and may vary depending on factors such as the timing of therapy initiation and individual risk factors ( Amirkashani et al, 2022 ).…”
Section: Introductionmentioning
confidence: 99%
“…The influence of traditional orthodontic appliances, such as brackets, on patients' aesthetic perceptions and quality of life has been widely studied. For example, Barrera-Chaparro and colleagues examined the orthodontic treatment need, types of brackets, and oral health-related quality of life, highlighting the importance of considering these factors in treatment planning [1].…”
Section: Introductionmentioning
confidence: 99%